Nonlinear thinking in the context of philosophical thought Нелинейное мышление в контексте развития философской мысли Нелінійне мислення в контексті розвитку філософської думки - T. V. Kichkiruk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
This article deals with the link between ideas and teachings of the philosophers of classical and non-classical periods of the history of philosophy and the provisions of the concept of non-linear thinking В статье исследуется связь между идеями и учениями философов классической и неклассической эпохи истории философии и положениями концепции нелинейного мышления. Досліджується зв’язок між ідеями і вченнями філософів класичної та некласичної доби історії філософії і положеннями концепції нелінійного мислення.